2019
DOI: 10.1109/access.2019.2937528
|View full text |Cite
|
Sign up to set email alerts
|

Amaru: Plug&Play Resilient In-Band Control for SDN

Abstract: Software-Defined Networking (SDN) is a pillar of next-generation networks. Implementing SDN requires the establishment of a decoupled control communication, which might be installed either as an out-of-band or in-band network. While the benefits of in-band control networks seem apparent, no standard protocol exists and most of setups are based on ad-hoc solutions. This article defines Amaru, a protocol that provides plug&play resilient in-band control for SDN with low-complexity and high scalability. Amaru fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Amaru [29] is a protocol that works for failure handling. It incarcerates the multi objectives (i.e., fast bootstrapping, topological scalability) in in-band SDN control.…”
Section: Related Workmentioning
confidence: 99%
“…Amaru [29] is a protocol that works for failure handling. It incarcerates the multi objectives (i.e., fast bootstrapping, topological scalability) in in-band SDN control.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, RSTP did not allow the synchronization of the HLMAC suffixes, which is explained in the following paragraphs as one of the enhancements provided by eTorii. Therefore, this labelling is performed by GA3 [10] in eTorii instead, which follows the principles of meshed trees [22,23]. The control frames of both RSTP and GA3 are illustrated in Figure 1.…”
Section: Auto-configuration: Automatic Label Assignment Based On Ga3mentioning
confidence: 99%
“…The flooding of GA3 frames is performed until all network nodes are reached. This process is not performed if the switches receive HLMACs longer than the ones previously obtained, as they discard them to avoid loops [22,23]. The resulting assignment is illustrated in Figure 2.…”
Section: Auto-configuration: Automatic Label Assignment Based On Ga3mentioning
confidence: 99%
“…Sharma et al [55], [56] compared the protection and recovery approaches for inband OpenFlow networks and concluded that only protection grants a recovery period under the required 50 ms as stipulated by Multiprotocol Lable Switching Transport Profile (MPLS-TP) requirements for network restoration after failure detection with spans less than approximately 746 miles [41]. A recent work by Lopez-Pajares et al [37], proposed Amaru, a protocol that provides plug-and-play resilient in-band control for SDN with low-complexity and high scalability. The protocol uses hierarchical labeling to mask MAC address to simplify the routing tables and minimize the number of entries to one per path.…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we trade off the simplicity of out-ofband for the quick update advantage of in-band operational mode [4], [12]. As summarized in [37], in-band control can easily scale with the size of the network without incurring high routing cost, and less prone to congestion due to the high capacity nature of the data plane links when compared to the out-of-band control. Further, the resiliency of in-band networks to link failure comes with no extra cost (i.e., providing secondary paths) since both data path and control path share the same link.…”
Section: Problem Formulationmentioning
confidence: 99%